The Determinants Self-Care of Diabetic Foot Ulcer Incidence Diabetes Mellitus Patients - Hamim, Nur; Rahmat, Nafolion Nur; Ro’isah; Narsih, Umi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: : Diabetic foot ulcers are a chronic complication of Diabetes Mellitus (DM) that often leads to disability and amputation. The incidence of foot ulcers is closely related to patient self-care behavior, including diet, physical activity, medication adherence, blood sugar monitoring, and foot care Objective: The purpose of this study was to determine the determinants of self-care on the incidence of diabetic foot ulcers in Diabetes Mellitus patients. Methods: This article used a cross-sectional design with a population of 91 with a sample of 73 DM patients selected by purposive sampling. The instruments used were the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire to assess self-care and an observation sheet for the incidence of diabetic foot ulcers. Data analysis was performed using the Chi-Square test and logistic regression to determine the determinant factors. Results: The results showed a significant relationship between self-care and the incidence of diabetic foot ulcers (p < 0.05). Foot care was the most dominant factor (OR = 0.0004; CI95%), followed by blood sugar monitoring and medication adherence. Conclusion: Self-care significantly influences the incidence of diabetic foot ulcers, with foot care being the primary determinant. Intensive education regarding self-care, particularly foot care and blood sugar monitoring, is needed to prevent further complications.